2018
DOI: 10.3390/s18051329
|View full text |Cite
|
Sign up to set email alerts
|

Textile Retrieval Based on Image Content from CDC and Webcam Cameras in Indoor Environments

Abstract: Textile based image retrieval for indoor environments can be used to retrieve images that contain the same textile, which may indicate that scenes are related. This makes up a useful approach for law enforcement agencies who want to find evidence based on matching between textiles. In this paper, we propose a novel pipeline that allows searching and retrieving textiles that appear in pictures of real scenes. Our approach is based on first obtaining regions containing textiles by using MSER on high pass filtere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 69 publications
0
15
0
6
Order By: Relevance
“…It has been widely used in carriers, such as robots. In [42][43][44][45][46][47][48], the latest image feature extraction and image retrieval technologies were discussed, along with an analysis of the state-of-the-art methods for image location recognition, using deep learning and visual positioning based on traditional image features. It was concluded that the positioning success rate of neural network models based on deep-learning training needs to be improved and that it is difficult for the positioning accuracy to reach the decimeter level.…”
Section: Related Workmentioning
confidence: 99%
“…It has been widely used in carriers, such as robots. In [42][43][44][45][46][47][48], the latest image feature extraction and image retrieval technologies were discussed, along with an analysis of the state-of-the-art methods for image location recognition, using deep learning and visual positioning based on traditional image features. It was concluded that the positioning success rate of neural network models based on deep-learning training needs to be improved and that it is difficult for the positioning accuracy to reach the decimeter level.…”
Section: Related Workmentioning
confidence: 99%
“…The proposed descriptor comprises two histograms jointly: a perceptual uniform histogram and a motif co-occurrence histogram including the probability of a pair of motif patterns. Finally, García-Olalla et al [13] proposed a method for textile based image retrieval for indoor environments based on describing the images with different channels (RGB, HSV, etc.) and using the combination of two different descriptors for the image.…”
Section: Contributions To the Special Issue On Visual Sensorsmentioning
confidence: 99%
“…In [15] writer attempted texture based image retrieval (TBIR) utilizing machine learning algorithms and their amalgamation including Faster Region based Convolution Neural Network (R-CNN), Adaptive Linear Binary Pattern (ALBP), Complete Local Oriented Statistical Information Booster (CLOSIB) Histogram of Oriented Gradients (HOG) and Half Complete Local Oriented Statistical Information Booster (HCLOSIB) for neighboring patch explanation of clothing. Their dataset is collected of 684 pictures of sizes that series between 480x360 and 1280x720 pixels gathered from 15 videos of YouTube.…”
Section: Related Workmentioning
confidence: 99%